Towards Broadcasting Linear Content over 5G Network - Shurdi, Olimpjon; Lala, Algenti (European Scientific Journal, ESJ, 2023)
Today's society relies heavily on linear television systems with planned programs, which are also a crucial form of communication. Broadcast of liner content is evolving, driven particularly by the evolution of end users’ devices, it is has changed from a small number of linear radio and TV channels to a comprehensive and distinctive offer that is available across a variety of various distribution platforms. Broadcasting linear content over 5G networks involves delivering scheduled, real-time content such as live TV broadcasts, radio programs, or streaming events to a large number of users simultaneously. While 5G networks offer significant advantages in terms of capacity, speed, and latency, there are specific considerations when it comes to broadcasting linear content. hassle cellular networks offering the discontinues services, have been predominantly built on a unicast bidirectional communication paradigm for many years, offering its end customers a variety of services. In this paper, we examine the future 3rd Generation Partnership Project (3GPP) 5G Multicast and Broadcast Services (MBS) standards as well as some of its constraints. We also outline the most recent standardization efforts aimed at bringing non-3GPP broadcast networks into the 5G system, along with the suggestions we have made to standards bodies.